Stability of Metallic Current Collectors in Acidic Ionic Liquid for Rechargeable Aluminum‐Ion Batteries. Issue 22 (12th October 2018) - Oh, Youngho; Lee, Gibaek; Tak, Yongsug
Abstract: Invited for this month's cover picture is the group of Prof. Gibaek Lee (Yeungnam University, Republic of Korea) and Prof. Yongsug Tak (Inha University, Republic of Korea). The cover picture shows the concept of finding the last piece to complete rechargeable aluminum‐ion batteries as one of the advanced energy storage systems. Read the full text of the Communication at10.1002/celc.201800892 . Abstract : " There are new insights into the roles of a Mo current collector as the new substitute for Ni in rechargeable aluminum‐ion batteries, exhibiting fairly stable and reversible redox cycling in the expanded potential window without any side effects or reactions, thus leading to the enhanced capacity at an extremely high current density for long‐term cycles …" Find out more about the story behind the front cover research at10.1002/celc.201800892 .